O uso das tecnologias assistivas: com ênfase em deficiência física, na sala do AEE em uma escola pública do município de Porto Grande no estado do Amapá - MACHADO, Alex de Moraes (Instituto Federal do Amapá, 2021)
It is considered that the world, with its sociais, technological and cultural representations, is modified with the advancement of Information and Communication Technologies (ICTs), in the different environments of interaction, with new technological resources and structural factors in the pedagogical conceptions. Therefore, the research aims to analyze the contributions of some authors related to the topic addressed, about the emerging problem, to achieve the proposed objectives that aim to provide access and participation to all involved with the use of methods for teaching practice with the use of Assistive Technology for the physically disabled, in Specialized Educational Service (AEE). We opted for bibliographic research, whose qualitative method to support the discussions that are indispensable. It provides us with a place for critical analysis and information production, with an articulation between systematized teaching, in order to obtain learning and mobility for the physically disabled in the space of the school in locus. Thus, there is a reflection of the objectives not achieved, in order to contribute with proposals for architectural improvements and the practice of teacher training with the physically disabled, in the Specialized Educational Service room.